CHARACTERIZATION OF A NEW PROTEIN AS A RESPONSIBLE FACTOR FOR THE RESISTANCE OF Phaseolus vulgaris TO Zabrotes subfasciatus (Boheman) (Coleoptera: Bruchidae) - POSSO, CARMEN E.; CARDONA, CÉSAR; VALOR, JOSÉ F.; MORALES, HÉCTOR (Revista Colombiana de Entomología, 1989)
Arcelin, a new protein, present only in wild beans resistant to Zabrotes subfasciatus, was evaluated as a possible antibiotic factor of resistance to this pest. When arcelin was introduced in cultivated susceptible beans by means of backcrosses, it was demonstrated that arcelin expression is controlled by single mendelian gen and its presence is dominant to its absence. Thus, dominant homozygous lines were highly resistant to the insect, while homozygous recessive lines were highly susceptible. Heterozygous lines were intermediate. The antibiotic effect of arcelin was demonstrated in artificial bean seeds containing increasing levels of the purified protein; the medium lethal concentration (LC50) was 6.50/o. The presence of arcelin can be used as a marker for resistance to the insect. A serological technique has been implemented to detect the protein in segregating populations of beans. Positive seeds are multiplied and evaluated for reaction to the insect in F3 and the following generations. This method is being utilized to obtain commercial beans resistant to Z. subfasciatus.